The Notion of Hatha Yoga: A Tantric Tradition in the Nath Panth of South Asian Religions and Cults - Kumar, Yogender; Chauhan, Manoj Kr Singh (International Research Journal of Ayurveda & Yoga, 2025)
The entire universe is created through the union of two opposite energies, and likewise, a human being is a manifestation of the confluence of these two similar forces. One is the energy of pure consciousness, referred to as Purusha or Shiva, residing in the Sahasrara Chakra at the crown of the head. The other is the energy of pure matter, known as Prakriti or Shakti, situated in the Muladhara Chakra in the pelvic region. These two energies exist at two opposite poles of the body—Shiva, representing the masculine tendency, while Shakti, embodying the feminine tendency, is the dynamic energy of material creation. Shiva symbolizes Yoga (union), whereas Shakti symbolizes Bhoga (manifestation). In the Natha tradition, during the practice of Hatha yoga, these masculine and feminine energies merge at a subtle level as the Shiva and Shakti. As for the physical intercourse, at the subtle spiritual level, the inner masculine (Shiva) and feminine (Shakti) unite in Samadhi-yoga, leading to the experience of supreme bliss. This state of supreme bliss is regarded as Moksha or Kaivalya (liberation). This article aims to emphasize that the human body is a living laboratory where, through the practice of Tantra yoga, one can not only uncover the deepest mysteries of the universe but also find profound solutions to all challenges related to human life. Understanding and harnessing this knowledge can help create a life that is harmonious, healthy, prosperous, fearless, compassionate, and deeply peaceful.